Development of Mathematics Learning Sets Based on Problem Solving on Two Variable Linear Equation System Topics - Alex Haris Fauzi; Firma Yudha (Indonesian Journal of Mathematics and Natural Science Education, 2022)
Temuan fakta di kelas yang ditunjang oleh data hasil survey PISA dan TIMSS menunjukkan bahwa masih rendahnya kemampuan siswa pada pemecahan masalah matematika. Hal ini disebabkan model pembelajaran yang digunakan belum bisa meningkatkan keaktifan siswa di kelas. Salah satu strategi yang dilakukan oleh guru adalah menggunakan pembelajaran berbasis masalah. Tujuan penelitian ini adalah mengembangkan perangkat pembelajaran dengan model pembelajaran berbasis masalah pada materi sistem persamaan liner dua variabel. Subjek penelitian ini adalah siswa kelas VIII di MTs Hidayatul Mubtadiin pada semester genap tahun pelajaran 2018/2019. Instrumen pengumpulan data yang digunakan adalah lembar validasi perangkat pembelajaran, lembar pengamatan kemampuan guru, lembar pengamatan aktivitas siswa, lembar angket respon siswa, dan tes hasil belajar. Hasil penelitian ini adalah perangkat pembelajaran yang dikembangkan berkategori valid, praktis, dan efektif. Findings of fact in class supported by data from TIMSS and PISA survey show that limited student's ability on problem-solving in mathematics. It is because no learning model is used to increase the liveliness of students in class. One of the strategies taken by learning by teachers was to utilize based problems. The purpose of this research is to develop with the device learning problems related to the matter-based for topic system a linear two variables. The subject of study is student of VIII in MTs Hidayatul Mubtadiin for odd semester 2018/2019 academic year. Instruments that gather the data used were sheets validation device learning, sheets observation of the capability of teachers, sheets observation students, activity sheets students survey response, and tests study results. The results of this research is the learning instrument that developed is valid, pragmatic,, and effective.